ENT 530: Keropok Ikan Segera Seameq / Muhammad Zaki Azid - Azid, Muhammad Zaki (2021)
Keropok Ikan Segera SEAmEQ are the first ever brand that created a ready to eat local traditional malay food Keropok Lekor. SEAmEQ put a little twist to it and named it Keropok Ikan Segera because of the ability to just eat it instead of the traditional one you need to deep fry them. SEAmEQ were established since 2008 and have been the ace in Keropok industry. They operation are based in Kuala Terengganu which make sense why they started this business. Ever since they launched the Keropok Ikan Segera, they have in total 5 flavor which are the original, curry, black pepper, garlic, and cheese. As for now they are operating through their official warehouse where people or retailer would come and buy their product. All the detail for each product you can get through their website www.seameqhq.com.